The Influence of Experiential Marketing and Facilities on Consumer Satisfaction at KFC Galuh Mas Karawang - Muhammad Aldi Rizky; Jakaria Jakaria (Managing: Jurnal Bisnis dan Manajemen, 2026)
This study aims to determine the effect of experiential marketing, emotional branding, and customer loyalty on customer satisfaction. This study used a quantitative approach with a survey method involving 99 respondents who were active consumers. The data analysis technique used multiple linear regression with the help of SPSS. The results showed that Experiential Marketing had a positive and significant effect on customer satisfaction. Emotional branding also had a significant impact, where emotional attachment to the brand increased satisfaction. Customer loyalty also had a significant impact, strengthening the relationship between consumers and the company. Simultaneously, these three variables contributed to increasing customer satisfaction. These findings indicate the importance of building a pleasant customer experience, strengthening emotional connections with the brand, and maintaining customer loyalty. Recommendations for companies include increasing innovation in Experiential Marketing, consistency in emotional branding, and developing sustainable customer loyalty programs to maintain customer satisfaction.